Design and Research of Smart Neck Helmets Based on the KANO-QFD Model and TRIZ Theory. (7th October 2021) - Zhao, Deng; Chen, Weiwei
Abstract : In order to better serve the safety protection of urban residents during cycling, the KANO model is used to analyze the problems encountered by users wearing helmets during cycling. Combined with QFD, the weighted average analysis of user needs and the importance of engineering measures of product technical characteristics is carried out and users are found. We used TRIZ innovative invention principles to analyze the key requirements and converted them into TRIZ standard problems. We used the corresponding invention measures to improve the existing problems of the helmet and verified the rationality of the design through finite element analysis. Through the KANO-QFD model combined with the TRIZ innovative invention principle, the helmet is optimized to improve its safety.